Public policies of affirmative actions: equality, solidarity, alterity – limits - Ferrari, Regina Maria Macedo Nery (Universidad Nacional del Litoral, 2016)
Seeking the realization of fundamental rights, the adoption of affirmative public policies, such as racial and socioeconomic quotas in higher education and in public competitions, has been increasing. This article focuses on the issue of affirmative actions in the formal, material and substantial equality plans, in order to establish the limits for its implementation.